Long non‐coding RNA analysis of muscular responses to testosterone deficiency in Huainan male pigs. (9th February 2017) - Xing, Baosong; Bai, Xianxiao; Guo, Hongxia; Chen, Junfeng; Hua, Liushuai; Zhang, Jiaqing; Ma, Qiang; Ren, Qiaoling; Wang, Huashuai; Wang, Jing
Abstract: Long non‐coding RNAs (lncRNAs) participated in growth and development of skeletal muscle; however, little is known about their response to testosterone deficiency in porcine skeletal muscle. We compared lean mass related carcass traits and lncRNAs expression files in Longissimus dorsi (LD) muscle between intact and castrated Huainan male pigs. The results showed that castration significantly reduced eye muscle area and lean meat percentage ( P < 0.05), but increased the fat mass weight ( P < 0.05). Meanwhile, 8946 lncRNAs, including 6743 intergenic lncRNAs (lincRNAs), 498 anti‐sense lncRNAs, and 1705 intronic lncRNAs, were identified in porcine LD, among which, 385 lncRNAs were considered as the differentially expressed candidates between intact groups and castrated groups ( q‐ value < 0.05). Functional analysis indicated that these differently expressed lncRNAs and their target genes were involved in the estrogen receptor signaling pathway and skeletal and muscular system development and function. We first detect porcine muscular lncRNA response to castration, and the results suggested that lncRNAs and their target genes participated in the regulation of testosterone deficiency‐related skeletal muscle growth.